Pemberdayaan Masyarakat Melalui Pengolahan Buah Nipah (Nypa Fruticans, Wurmb) Menjadi Berbagai Produk Olahan Dan Pembentukan Sentra Industri Kecil Di Kecamatan Langsa Timur Kota Langsa - Juanda, Boy Riza; Risyad, Syukri; Hanisah, Hanisah (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
This program is designed to answer the problem of unavailability of potential human resources in processingand utilizing the potential of local raw materials as a business that can be developed to increase the income of localfarmers. With the implementation of this pioner program, the training is designed, Establishment of Joint Business Group"KUBE" and Opening and expanding partner marketing network for farmer group of Sungai Lueng village "TunasHarapan" and farmer group "Karya Bersama" Sukarejo village. Training materials include processing of nipah productssuch as dodol products, candied nipah, and nipah fruit syrup. The whole process of science and technology transferplanned to be implemented with the pattern of education and training and mentoring which include: socialization,training, and assistance to farmer groups of Sungai Lueng village "Tunas Harapan" and farmers group "KaryaBersama" Sukarejo village